Soft-shell headgear in rugby union: a systematic review of published studies - Henley, S.; Andrews, K.; Kabaliuk, N.; Draper, N. (Sport Sciences for Health, 2023)
Objectives To review the rate of soft-shell headgear use in rugby union, consumer knowledge of the protection potential of soft-shell headgear, incidence of concussion reported in rugby headgear studies, and the capacity of soft-shell headgear to reduce acceleration impact forces.